MODIFICATION OF ILIZAROV BONE EXTERNAL FIXATION - Sitompul, Eric
Fractures are a serious problem that must be handled, because it can lead to disability. Through surgery, the bone can be reconnected, but it takes time for bones to grow and can be used as before. During the recovery period, it’s needed tools to keep your bones remain stable during the recovery period and the person who use it still able to move lightly. Such a device can be either simple fixation or Ilizarov fixation. Ilizarov external fixation is a tool invented by Gavril Abramovich Ilizarov,a surgeon from the Soviet Union. Ilizarov bone fixation is device with a wire as the support of the bone with a bone spacer system that more flexible than the other bone fixation devices. Its function is to keep the bone in order not to receive excessive loading during the activity and keeps the bones remained stable during the growth or recovery. With that way, the bone will grow almost perfectly as usual. Even so, tools that have been used until now, still less convenient to use by physicians, there are still some trouble that caused the tool less practical and making it difficult for doctors in the installation and treatment. It is needed some modifications to the Ilizarov so it will much easier for physicians in using those tools. Therefore, new designing of some components is going to do, in order to make it more practical without changing the main functions of its components.